PENGARUH POLITIK ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOUR KARYAWAN KOPERASI KARYAWAN (KOPKAR) SAMPOERNA SURABAYA - FIRDAUS RURI PRADANA, AHMAD (Jurnal Ilmu Manajemen (JIM), 2016)
Political organization is a social reality that must be faced by members of the organization in which they will involve interaction with one another. This study aimed to analyze the influence of political organizations and organizational commitment on Organizational Citizenship Behaviour (OCB). The samples in this study using Stratisfield Proportional Random Sampling design. The sample consisted of 60 respondents Kopkar employees of Sampoerna Surabaya. The data collection is done by using a questionnaire. After that tested the validity, reliability and data analysis technique processed using SPSS version 18.The results of this study show that organizations Political significant positive effect on Organizational Citizenship Behaviour, organizational commitment has no effect on Organizational Citizenship Behaviour, Simultaneously, political organizations and organizational and commitment significantly influence Organizational Citizenship Behaviour of employees amounted to 40,9%, while the remaining 59,1% is explained by other factors. Keywords:Political organizations, Commitment organizations, and Organizational Citizenship Behaviour.